2010
DOI: 10.15517/rbt.v58i4.5420
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of phytoplankton in a small tropical crater lake, Costa Rica

Abstract: Abstract:The temporal variation in lake's phytoplankton is important to understand its general biodiversity. For tropical lakes, it has been hypothesized that they follow a similar pattern as temperate ones, on a much accelerated pace; nevertheless, few case studies have tried to elucidate this. Most studies in Costa Rica have used a monthly sampling scheme and failed in showing the expected changes. In this study, the phytoplankton of the small Barvas's crater lake was followed for more than three years, firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Additionally, the findings of this study suggest that significant rainfall variations cause extreme seasonal surface runoff and rapid changes in the water quality (Chlorophyll- a , DO, NH 4 + , and NO 3 – ) of this subtropical lake, as well as rapid variations in the phytoplankton community ( Figures 3 , 2 , 5 , 7 ). Studies on the temporal variations in the phytoplankton community have been carried out in temperate regions, but only a few have been reported in tropical or subtropical regions, such as Lake Cajititlán ( Limón-Macias et al, 1983 ; Umaña-Villalobos, 2010 ; Riediger et al, 2015 ; Li et al, 2018 ; Ma et al, 2019 ; Quevedo-Castro et al, 2019 ). The wet season in tropical and subtropical areas exacerbates the cultural eutrophication of surface water bodies when there is intensive agricultural activity in their basin ( Barbosa, 2009 ; Cunha et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the findings of this study suggest that significant rainfall variations cause extreme seasonal surface runoff and rapid changes in the water quality (Chlorophyll- a , DO, NH 4 + , and NO 3 – ) of this subtropical lake, as well as rapid variations in the phytoplankton community ( Figures 3 , 2 , 5 , 7 ). Studies on the temporal variations in the phytoplankton community have been carried out in temperate regions, but only a few have been reported in tropical or subtropical regions, such as Lake Cajititlán ( Limón-Macias et al, 1983 ; Umaña-Villalobos, 2010 ; Riediger et al, 2015 ; Li et al, 2018 ; Ma et al, 2019 ; Quevedo-Castro et al, 2019 ). The wet season in tropical and subtropical areas exacerbates the cultural eutrophication of surface water bodies when there is intensive agricultural activity in their basin ( Barbosa, 2009 ; Cunha et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as precipitation and wind are the main seasonal drivers of change in the tropics (Lewis, 1996), and these affect the stratification of the lakes, even at short times scales (Talling & Lemoalle, 1998), other authors have found that there are shifts in the species composition according to shifts in precipitation (Figueredo & Giani, 2001;González, Ortaz, Peñaherrera, & Matos, 2004). In other Costa Rican lakes, where phytoplankton composition has been evaluated weekly for at least one year (Arenal, Barva, Fraijanes, Bonilla), the situation has shown that this sequence not always occurs, and that changes are mainly in the relative contribution of dominant species, rather than a complete change in species composition (Umaña & Collado, 1990;Umaña-Villalobos, 2010, 2014, 2016. Lopez, Bicudo, and Ferragut (2005) also found a shift in relative contribution of a few dominant species in a shallow subtropical reservoir in Brazil, and González et al (2004) also reported a similar pattern of small changes in the relative contribution of a few dominant species in El Salto Reservoir, Venezuela.…”
Section: Discussionmentioning
confidence: 99%
“…In Costa Rica there are a few studies focused on zooplankton variations. For example, in Fraijanes Lake there is a study about zooplankton variations for one year (Umaña-Villalobos, Avilés-Vargas, & Esquivel-Garrote, 2018) and in Barva Lake there is a study about the phytoplankton variations for one year (Umaña-Villalobos, 2010).…”
mentioning
confidence: 99%
“…Studies on marine environments prevail in Costa Rica (Suárez- Morales and Gasca, 1989;Morales and Vargas, 1995;Brugnoli-Olivera et al 2004;Morales-Ramírez et al, 2014;Décima et al, 2016), while our knowledge of inland waters is based on only very few studies. Some data exist on phytoplankton (Haberyan et al, 1995;Umaña, 2001;Umaña-Villalobos, 2010;Landry et al, 2016). However, information on animal plankton is still very scarce (Dumont, 1994;Morales-Ramírez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%